(untitled) (LEARNing Landscapes, 2023)
In this paper, we draw upon a narrative inquiry alongside two creators of an out-of-doors Nipugtugewei Kindergarten program within a Mi’gmaw community, in northeastern Canada. Our intention was to understand their schooling, educational, and communal experiences over time. Diverse field texts were composed and interpreted alongside participants. We turned towards narrative conceptions of knowledge to show how attending to teachers’ personal practical knowledge and stories to live by on their professional knowledge landscape is sustaining who they are as teachers and people. It is also a way for teachers to live their responsibility to Indigenous communities and students.